Highly effective hydrogen isotope separation by cryogenic gas chromatography in a new stationary phase material MnCl2@CPL-1@γ-Al2O3. (19th April 2018) - Yang, Shaowei; Xie, Hui; Zhu, Hongwei; Zhang, Lijuan; Zhou, Yunshan; Zhang, Huixian; Zhao, Zipeng
Abstract: In this work, metal-organic framework compound CPL-1 of a formula {[Cu2 (pzdc)2 (pyz)]⋅2H2 O}n (pzdc = pyrazine-2, 3-dicarboxylate, pyz = pyrazine) possessing kinetic quantum sieving effect on H2 /D2 separation was selected to prepare two new chromatography stationary phase materials CPL-1@γ-Al2 O3 and MnCl2 @CPL-1@γ-Al2 O3 by loading CPL-1 on γ-Al2 O3 particles with size 80–100 mesh through repeating in situ crystallization process, and afterwards by loading MnCl2 on CPL-1@γ-Al2 O3 via impregnation approach. The two optimized materials were thoroughly characterized by IR, XRD, SEM, EDS and TG/DTA method. The experimental results showed that, under liquid nitrogen temperature by using just 1-m chromatographic column and cheap He gas as carrier gas, the MnCl2 @CPL-1@γ-Al2 O3 can solve the problem of long separation time and trailing phenomenon existing in the CPL-1@γ-Al2 O3 column, can realize highly effective hydrogen isotope H2 /D2 separation with good separation resolution (R = 1.62) and approximate Gauss distribution of chromatographic peak, can be used for both qualitative and quantitative analysis of hydrogen isotope H2 /D2 with short separation time of 6.5 min. Graphical abstract: Highlights: Two materials CPL-1@γ-Al2 O3 and MnCl2 @CPL-1@γ-Al2 O3 are prepared and characterized. The materials are used as stationary phase materials under liquid N2 temperature. The materials are loaded into a 1-m chromatographic column. H2 /D2 can be effectively separated for both qualitative and quantitative analysis. Loading MnCl2 into CPL-1@γ-Al2 O3 can resolve chromatography-tailing phenomenon.